Effect of indium doping in CdO thin films prepared by spray pyrolysis technique - Kumaravel, R.; Ramamurthi, K.; Krishnakumar, V. (The Journal of physics and chemistry of solids, 2010)
Preparation of transparent and conducting indium doped CdO thin films by spray pyrolysis on glass substrate is reported for various concentration of indium (2–8 wt%) in the spray solution. The electrical, optical and structural properties of indium doped CdO films were investigated using different techniques such as Hall measurement, optical transmission, X-ray diffraction and scanning electron microscope. X-ray analysis shows that the undoped CdO films are preferentially orientated along (2 0 0) crystallographic direction. Increase of indium doping concentration increases the films packing density and reorient the crystallites along (1 1 1) plane. A minimum resistivity of 4.843×10 −4 Ω cm and carrier concentration of 3.73×10 20 cm −3 with high transmittance in the range 300–1100 nm were achieved for 6 wt% indium doping. The band gap value increases with doping concentration and reaches a maximum of 2.72 eV for 6 wt% indium doping from 2.36 eV of that of undoped film. The minimum resistivity achieved in the present study is found to be the lowest among the reported values for In-doped CdO films prepared by spray pyrolysis method.